Indian influences in Malay films of the golden era : Dewi Murni, Gul Bakawali and Selendang Delima / Sumathi Maniam - Maniam, Sumathi (2014)

(untitled)
The purpose of this study is to establish that the Malay movies Dewi Murni (Shakuntala) 1950 directed by B.S. Rajhans, Selendang Delima 1958 directed by K.M. Basker, Gul Bakawali (Gule Bagawali) 1963 directed by B. Narayanan Rao are influenced by Indian elements. In establishing this theory, the influence of the Indian culture, the history of the Malay films in connection with Bangsawan and the influence of the Indians in channeling its course are examined in my research. I have discovered that there are similarities between the story line of Dewi Murni and Kalidasa’s Shakuntala, Gul Bakawali which is sourced from a Persian story translated to Hindustani ( Zainal Abidin Ahmad, 1942:144) in the year 1702 by Niphal Chand. The person who translated Gul Bakawali from an Urdu / Hindi text was Sheikh Mohd. Ali bin Ghulam Hussein Alhandi (an Indian Muslim) who was residing in Singapore. As for Selendang Delima, it tells the tale of a nymph’s daughter who is cursed and has to go through hardships on earth. This form of story that deals with the supernatural element is indeed Indian in origin. The research aims to prove that films proposed for study were heavily embedded with Indian influences in their stories, characterization, themes as well in aesthetic elements. These Indianised elements were instrumental in ensuring the success of the films. The research also aims to provide evidence that pluralism and cultural syncretism was evident in the cinemas of Malaya and Singapore in the golden era